Tipología de las transgresiones ambientales urbanas y sanciones administrativas en la ciudad de Tamshiyacu, distrito de Fernando Lores – 2023 - Salate Pitta, Gianella Ximena (2023)
The thesis was executed in the city of Tamshiyacu, Fernando Lores District, with the objective of understanding and evaluating the environmental inspection, as well as the components that affect the imposition of corrective measures within the framework of the corrective administrative process. It is quantitative research. non-experimental, descriptive, analytical, horizontal level. The secondary information was obtained from the records of the environmental transgressions of the Public Services Management, the hypothesis test was made with the Pearson Chi Square statistic and according to the result the Hypothesis of the study is accepted, concluding that the inspection-intervention environmental, is managing to reduce environmental transgressions, as well as the application of sanctions, in the population of Tamshiyacu, District of Fernando Lores, with a 95 percent confidence. Thus, the evidence shows that the environmental transgressions in the years evaluated, 2020, 2021 and 2022, have a tendency to decrease year after year, presenting the year 2020 with the highest number of transgressions decreasing in the following years.